Czas pracy nauczycieli w polskiej debacie publicznej - Dzierzgowski, Jan (Wydawnictwo Naukowe UAM, 2015)
The following paper presents findings of an analysis of public debates concerning teachers’ workload in Poland. The main conclusion states that the key subject of the aforementioned debates are the group interests of various actors participating in it. Debates concerning teachers’ workload is merely a pretext for delegitimizing other actors by stating that they do not attempt to serve the common good, but instead do what is good for them. In addition, on the basis of the debates analyzed it is possible to reconstruct a particular discourse concerning demands (of certain actors partaking in the debates) on the central government’ policymaking strategies.
Teachers’ Workload in Polish Public Debates
Keywords: discourse analysis; teachers’ workload; group interests